Antibacterial effect of alpha-mangostin from Garcinia mangostana. L against oral streptococci and staphylococci biofilms: a systematic review - Praptiningsih, Rahmawati Sri; Siswomihardjo, Widowati; Jonarta, Alma Linggar; Yulianto, Heribertus Dedy Kusuma; Syifa, Liftia Layyinatus; Rochmah, Yayun Siti; Ichwan, Solachuddin Jauhari Arief (Padjadjaran Journal of Dentistry, 2024)
ABSTRACTIntroduction: Interactions among competing bacteria, which inhibit each other's growth to maintain the balance of microorganisms in the biofilm, can influence oral cavity homeostasis. Natural products contain compounds with the potential to combat various diseases, including caries. Alpha-mangostin from Garcinia mangostana. L exhibits antibacterial properties against oral streptococci and staphylococci, acting through several mechanisms, including the disruption of peptidoglycan, which ultimately leads to cell brittleness and rupture. This study aims to assess the impact of antibacterial alpha-mangostin on oral streptococci and staphylococci biofilm. Methods: The research methodology employed secondary data collection through a systematic review study. We conducted searches across databases including PubMed, ScienceDirect, and Google Scholar to identify Indonesian and English references encompassing textbooks, research findings, reviews, and internet articles relevant to the topic published between 2014 and 2024. Following a thorough screening process, we selected articles deemed pertinent for inclusion in the review. Subsequently, these articles underwent evaluation for full-text accessibility, language compatibility, and availability of information from the respective journals, resulting in the selection of 20 articles. Results: Analysis was carried out on 20 articles. Ten articles described the effects of alpha-mangostin's inhibit oral biofilm, 6 articles discussed the effects of alpha-mangostin's antibacterial activity against Streptococcus mutans and Streptococcus sanguis, 3 article state mechanism alpha-mangostin inhibit membrane enzymes such as F(H+)-ATPase and the phosphoenolpyruvate-sucrose phosphotransferase system on Staphylococcus aureus. Additionally, one article described inhibition mechanisms of aldolase, glyceraldehyde-3-phosphate dehydrogenase, and lactic dehydrogenase on Staphylococcus epidermidis. Conclusion: Alpha-mangostin inhibits and disrupts biofilm defense mechanisms. It possesses antimicrobial properties effective against oral streptococci and staphylococci, including Streptococcus mutans, Streptococcus sanguis, Staphylococcus aureus and Staphylococcus epidermidis. These properties operate through various mechanisms, including enhancing the permeability of bacterial cell walls, ultimately leading to bacterial cell death.KEYWORDSOral biofilm, alpha-mangostin, oral streptococci, staphylococci